The Strengthening of Students’ Character through Multiple Intelligences-Based Aqidah Akhlak Learning Strategies - Hilmi Asrori; Wasith Achadi (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the strengthening of students’ character through a multiple intelligences-based learning strategy in Aqidah Akhlak learning at MTs Negeri 4 Bantul. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. The research subjects included the head of the madrasah, Aqidah Akhlak teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The results show that the implementation of multiple intelligences-based learning strategies in Aqidah Akhlak learning is carried out through three main stages: learning planning, learning implementation, and character strengthening. In the planning stage, teachers prepare learning instruments by integrating various learning activities that accommodate the diversity of students’ intelligences. In the implementation stage, teachers apply active learning methods such as group discussions, presentations, case analysis, and reflective learning activities that encourage active student participation. These strategies contribute to strengthening students’ character values such as responsibility, discipline, cooperation, honesty, and mutual respect. The findings indicate that multiple intelligences-based learning strategies can create a more interactive, contextual, and character-oriented learning process.